Dynamic cataloguing of the old Arabic manuscripts by automatic extraction of metadata. Issue 2 (19th June 2017) - Soualah, Mohammed Ourabah; Ait Ali Yahia, Yassine; Keita, Abdelkader; Guessoum, Abderrezak
Abstract : Purpose: The purpose of this paper is to obtain online access to the digitised Arabic manuscripts images, which need to use a catalogue. The bibliographic cataloguing is unsuitable for old Arabic manuscripts, and it is imperative to establish a new cataloguing model. In the research, the authors propose a new cataloguing model based on manuscript annotations and transcriptions. This model can be an effective solution to dynamic catalogue old Arabic manuscripts. In this field, the authors used the automatic extraction of the metadata that is based on the structural similarity of the documents. Design/methodology/approach: This work is based on experimental methodology. The whole proposed concepts and formulas were tested for validation. This, allows the authors to make concise conclusions. Findings: Cataloguing old Arabic manuscripts faces problem of unavailability of information. However, this information may be found in another place in a copy of the original manuscript. Thus, cataloguing Arabic manuscript cannot be done in one time, it is a continual process which require information updating. The idea is to make a pre-cataloguing of a manuscript, then try to complete and improve it through a specific platform. Consequently, in the research work, the authors propose a new cataloguing model, which the authors call "Dynamic cataloguing". Research limitations/implications: The success of the proposed model is confronted with the involvement of all actors of the model. It is based on the conviction and the motivation of actors of the collaborative platform. Practical implications: The model can be used in several cataloguing fields, where the encoding model is based on XML. The model is innovative and implements a smart cataloguing model. The model is useful by using a web platform. It allows an automatic update of a catalogue. Social implications: The model prompts the user to participate and enrich the catalogue. The user could improve his social status from a passive to an active. Originality/value: The dynamic cataloguing model is a new concept. It has never been proposed in the literature until now. The proposed cataloguing model is based on automatic extraction of metadata from user annotations/transcription. It is a smart system which automatically updates or fills the catalogue with the extracted metadata.